1989
DOI: 10.1056/nejm198910263211704
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency and Natural History of Diabetes Insipidus in Children with Langerhans-Cell Histiocytosis

Abstract: Diabetes insipidus is a well-recognized complication of Langerhans-cell histiocytosis (histiocytosis X), but its frequency and natural history are not well defined. Of 52 children with histiocytosis whom we studied, 12 (23 percent) had diabetes insipidus. Only two children had diabetes insipidus at presentation with histiocytosis, but the cumulative risk that it would develop during the first four years after the presentation and diagnosis of histiocytosis was found to be 42 percent. Diabetes insipidus occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
2
4

Year Published

1996
1996
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(93 citation statements)
references
References 24 publications
4
83
2
4
Order By: Relevance
“…2,10 These cases are typically referred to neurosurgeons for resection. The question of whether to subject children with solitary calvarial EGs to surgery and its associated complications when these lesions may resolve spontaneously remains unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…2,10 These cases are typically referred to neurosurgeons for resection. The question of whether to subject children with solitary calvarial EGs to surgery and its associated complications when these lesions may resolve spontaneously remains unanswered.…”
Section: Discussionmentioning
confidence: 99%
“…DI is the most frequent initial sign of LCH in the CNS. 49 In children with isolated DI and a thickened pituitary stalk, the most likely diagnoses are LCH, germ cell tumor, or lymphoma. 50 LCH is frequently a diagnosis of exclusion with normal germ cell markers and normal CSF cytology.…”
Section: Brain Mri For Patient With Cns-risk Lesionsmentioning
confidence: 99%
“…Such conditions have also been described as partial, transient, or subclinical CDI. In one trial with 21 LCH patients who did not have CDI and had had LCH for less than four years (11), when the response of urinary AVP to water deprivation was measured every six months, it was found that 24% had subnormal responses during the initial test and CDI subsequently developed in two. However, it seemed difficult to predict precisely when CDI develops.…”
Section: Detection Of Partial CDImentioning
confidence: 99%